PENGARUH PENERAPAN STRATEGI GENIUS LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII.7 MTsN DANGUNG-DANGUNG KABUPATEN LIMA PULUH KOTA - Nurke, Asiah; Anggraini, Villia; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The background of the research are the studentsâ mathematical concept apprehension, leading to their low mathematical points. The purposes of this research is to know whether the studentsâ mathematical concept apprehension by applying the Genius Learning strategy is better than the conventional learning for the VII-grade students of MTsN Dangung-Dangung. This is an experimental research. The technique of sampling is by considering the existing characteristics and the sampling is purposive samples. The samples are taken in the purpose of improving the studentsâ mathematical concept apprehension and improving their learning completion. The instrument used in this research is the final test. The points of learning result for the students are processed with the Mann-Whitney test by using the final test data with the indicator of concept apprehension. The analysis is made by the assistance of Minitab and provides the probability value of 0.3197. It is shown that the probability is > Î±. So that the hypothesis put forward is rejected on the trust level of 95%. It is concluded that the studentsâ mathematical concept apprehension by applying the Genius Learning strategy is similar with that using the conventional learning for the VII-grade students of MTsN Dangung-Dangung in the year 2012/2013.